2008
DOI: 10.1103/physreve.77.031104
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the potential of mean force from nonequilibrium measurements via maximum likelihood estimators

Abstract: We present an approach to the estimate of the potential of mean force along a generic reaction coordinate based on maximum likelihood methods and path-ensemble averages in systems driven far from equilibrium. Following similar arguments, various free energy estimators can be recovered, all providing comparable computational accuracy. The method, applied to the unfolding process of the α-helix form of an alanine deca-peptide, gives results in good agreement with thermodynamic integration.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…Unidirectional estimates of ΔF t based on Jarzynski's equality are markedly biased as the states are further perturbed from the starting equilibrium state. Chelli and coworkers have also developed an asymptotically correct bidirectional estimator that reduces to BAR at the end states [26]. However, the derivation offered by these authors is limited to deterministic systems, and although we have empirical evidence that their estimator approaches the correct ΔF t for Brownian simulations in the limit of a large number of trajectories (data not shown), it leads to a more pronounced bias than Eq.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Unidirectional estimates of ΔF t based on Jarzynski's equality are markedly biased as the states are further perturbed from the starting equilibrium state. Chelli and coworkers have also developed an asymptotically correct bidirectional estimator that reduces to BAR at the end states [26]. However, the derivation offered by these authors is limited to deterministic systems, and although we have empirical evidence that their estimator approaches the correct ΔF t for Brownian simulations in the limit of a large number of trajectories (data not shown), it leads to a more pronounced bias than Eq.…”
mentioning
confidence: 82%
“…Since a general derivation of the results of Ref. [26] is not yet available, at present it is difficult to identify the source of discrepancy between these two estimators, and we leave this question for future investigations.…”
mentioning
confidence: 99%
“…[49][50][51] As we said, the free energy difference between two states can be evaluated through the WFT as F = W * , where W * is the work value such that P F (W * ) = P B (−W * ). More generally, it has been shown that a bidirectional approach, in which the number of available experiments is partitioned between the forward and the backward transformations is statistically more founded.…”
Section: Steered Molecular Dynamicsmentioning
confidence: 99%
“…The MLE is an iterative method that weights the measurements to remove statistical bias and minimize the subsequent variance [28][29][30][31] …”
Section: Improving On Exponential Samplingmentioning
confidence: 99%